Hoktiwe (for L. Rain Prud’homme-Cranford) - Darensbourg, Jeffery U. (Transmotion, 2020)
This is a cento composed using extracted sentences from both the 1932 and 2019 published dictionaries of Ishakkoy, also known as Atakapan, a dormant Indigenous language from Louisiana and Texas. The corpus of texts in the language is small, however the published materials have hundreds of example sentences. These were extracted and used to make new compositions, presenting a model for corpus expansion and creative composition in an Indigenous language.